2022
DOI: 10.1097/mlr.0000000000001755
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Affordable Health Care

Abstract: Background: Lack of affordable health care affects the uninsured, commercially insured, and Medicare beneficiaries. Yet, the wide variation in providers’ prices and practice styles suggests that more affordable care already may be available and data on low value and wasteful care suggest that lower cost care need not come at the expense of better quality. Although price variation has received the most attention in the literature and legislation, total cost of care is a function of both unit prices (fees) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The health expenditure is driven by volumes, price or their interplay [ 2 ]. While some studies suggested that utilization is the primary factor accounting for health expenditure [ 3 , 4 ], others contended that prices are the main contributing factor [ 5 , 6 ]. Developed and developing countries have implemented cost containment policies that target price as common strategies to control the rapid growth of health expenditures [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health expenditure is driven by volumes, price or their interplay [ 2 ]. While some studies suggested that utilization is the primary factor accounting for health expenditure [ 3 , 4 ], others contended that prices are the main contributing factor [ 5 , 6 ]. Developed and developing countries have implemented cost containment policies that target price as common strategies to control the rapid growth of health expenditures [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nal price that users pay for health services varies according to the speci c services and treatments received [3]. Professional, pharmaceutical, hospital and outpatient services are the main contributors to the average cost of health care [4]. Variability in nal prices can affect access to health care, particularly for people with limited resources, who may nd it di cult to meet health insurance co-payments [5].…”
Section: Introductionmentioning
confidence: 99%